Keberlanjutan Perusahaan: Pengaruh Biaya Lingkungan terhadap Kinerja ESG dan pada Kinerja Keuangan Perusahaan Sektor Energi - Doni Stiadi; Meina Wulansari Yusniar; Redawati Redawati; Fahmi Roy Dalimunthe (JWM (JURNAL WAWASAN MANAJEMEN), 2026)
Sustainability issues have become a major concern as stakeholders increasingly focus on companies responsible for environmental sustainability. ESG performance is increasingly used as an indicator to assess a company's commitment to sustainability practices. This study aims to analyze the influence of Environmental Costs on ESG Performance and Financial Performance, as well as the influence of ESG Performance on Financial Performance in energy sector companies listed on the Indonesia Stock Exchange (IDX). The sample was selected using a purposive sampling method from 89 energy sector companies for the 2021-2024 period, resulting in 27 companies meeting the research criteria, resulting in 108 data observations. A quantitative approach with causality was used in this study. Data analysis used simple and multiple linear regression to examine the influence of Environmental Costs and ESG Performance on Financial Performance. The results showed that Environmental Costs had a positive influence on ESG Performance, but an insignificant effect on Financial Performance. Other results indicated that ESG Performance had a positive influence on Financial Performance. These results indicate that environmental expenditures reflect a company's commitment to meeting stakeholder expectations regarding environmental sustainability, and that companies that effectively manage environmental, social, and governance aspects are able to achieve better economic benefits. A company's success in meeting the needs of various stakeholder groups can increase trust, customer loyalty, investor relations, and regulatory support, which ultimately will enhance the company's sustainable growth.